2021
DOI: 10.1192/j.eurpsy.2021.1214
|View full text |Cite
|
Sign up to set email alerts
|

The influence of concentration of micro-rna hsa-mir-370-3p and CYP2D6*4 on equilibrium concentration of mirtazapine in patients with major depressive disorder

Abstract: IntroductionMirtazapine is commonly prescribed to patients diagnosed with major depressive disorder.Some proportion of these patients do not show adequate response to treatment regimen containing mirtazapine, whereas many of them experience dose-dependent adverse drug reactions.ObjectivesThe objective of our study was to investigate the influence of 1846G>A polymorphism of the CYP2D6 gene on the concentration/dose indicator of mirtazapine, using findings on enzymatic activity of CYP2D6 and on CYP2D6 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It is reported that hsa-miR-370-3p is closely related to affective disorders such as depression [ 35 ]. And then, we detected the expression of miR-370-3p after overexpression of circIgfbp2 or knockdown of circIgfbp2.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that hsa-miR-370-3p is closely related to affective disorders such as depression [ 35 ]. And then, we detected the expression of miR-370-3p after overexpression of circIgfbp2 or knockdown of circIgfbp2.…”
Section: Resultsmentioning
confidence: 99%